2010
DOI: 10.1111/j.1469-8986.2010.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cycling exercise on vigor, fatigue, and electroencephalographic activity among young adults who report persistent fatigue

Abstract: We previously reported that 6 weeks of exercise training had positive effects on feelings of vigor and fatigue among college students who reported persistent fatigue. Here we examined whether transient mood changes after single sessions of exercise would mimic those chronic effects and whether they would be related to changes in brain activity measured by electroencephalography (EEG). Feelings of vigor were higher after both low- and moderate-intensity exercise during Weeks 1, 3, and 6 compared to a control co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 87 publications
1
38
0
Order By: Relevance
“…However, to date, few studies have addressed potential mechanisms of the relationships between energy and fatigue and physical activity behaviors, and to our knowledge, no studies have examined mechanisms of the relationship between sedentary behavior and these mood states. Recently, Dishman et al (12) examined whether changes in feelings of energy and fatigue following acute exercise after 6 wk of aerobic training were related to changes in brain activity as measured by electroencephalography. Results demonstrated that theta activity in the posterior portion of the brain accounted for approximately 50% of the improvement in mood immediately postexercise and that these improvements were unrelated to changes in aerobic fitness during the course of the training trial (40).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, to date, few studies have addressed potential mechanisms of the relationships between energy and fatigue and physical activity behaviors, and to our knowledge, no studies have examined mechanisms of the relationship between sedentary behavior and these mood states. Recently, Dishman et al (12) examined whether changes in feelings of energy and fatigue following acute exercise after 6 wk of aerobic training were related to changes in brain activity as measured by electroencephalography. Results demonstrated that theta activity in the posterior portion of the brain accounted for approximately 50% of the improvement in mood immediately postexercise and that these improvements were unrelated to changes in aerobic fitness during the course of the training trial (40).…”
Section: Discussionmentioning
confidence: 98%
“…Results from population-based studies are uniformly supportive of a positive dose-response relationship between self-reported participation in exercise and feelings of energy (6,27). Studies involving both acute and chronic exercise interventions have also shown significant benefits for both energy and fatigue in individuals with persistent fatigue (12,(39)(40)(41). Exercise interventions in nonfatigued adults have been less conclusive with results, either demonstrating positive effects of exercise or no change (2,5).…”
mentioning
confidence: 83%
“…Along with these, it may be expected that fatigue will occur as a result of a single bout of exercise, where a chronic training program could help reduce fatigue over a longer period of time. 76 The time when fatigue levels are reported could also have an impact on the results. Further research using similar populations and equipment could provide more consistent results for the effect of acute aerobic exercise on fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The combined score indicates the state level of fatigue and can be compared at selected time points during a protocol. For example, Dishman et al (14) used the Profile of Mood States fatigue scale to compare the influence of cycling exercise on the state level of fatigue in individuals who reported an elevated trait level of fatigue. Participants were assigned to either a 6-wk intervention (low- or moderate-intensity cycling) or a control group.…”
Section: Translating Fatigue To Performancementioning
confidence: 99%